2023
DOI: 10.1126/sciadv.ade3888
|View full text |Cite
|
Sign up to set email alerts
|

USP7 represses lineage differentiation genes in mouse embryonic stem cells by both catalytic and noncatalytic activities

Abstract: USP7, a ubiquitin-specific peptidase (USP), plays an important role in many cellular processes through its catalytic deubiquitination of various substrates. However, its nuclear function that shapes the transcriptional network in mouse embryonic stem cells (mESCs) remains poorly understood. We report that USP7 maintains mESC identity through both catalytic activity–dependent and –independent repression of lineage differentiation genes. Usp7 depletion attenuates SOX2 levels and derepress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…We speculate that USP7 activity might affect FOXL2 recruitment to DNA, stabilizing this interaction and thus allowing the differentiation of granulosa cells in wild-type prepubertal ovaries. Because our ChIP-SICAP experiment allows for detection of proteins colocalizing on the same chromatin regions, it is also plausible that USP7 may not directly bind to FOXL2, but it could be enriched in the same chromatin regions, possibly contributing to gene regulation as shown in other systems, for example, mouse embryonic stem cells differentiation ( 97 ) and early adipogenesis ( 98 ). We noted that the Usp7 gene was expressed throughout ovarian development to similar levels as of Foxl2 .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that USP7 activity might affect FOXL2 recruitment to DNA, stabilizing this interaction and thus allowing the differentiation of granulosa cells in wild-type prepubertal ovaries. Because our ChIP-SICAP experiment allows for detection of proteins colocalizing on the same chromatin regions, it is also plausible that USP7 may not directly bind to FOXL2, but it could be enriched in the same chromatin regions, possibly contributing to gene regulation as shown in other systems, for example, mouse embryonic stem cells differentiation ( 97 ) and early adipogenesis ( 98 ). We noted that the Usp7 gene was expressed throughout ovarian development to similar levels as of Foxl2 .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we know that USP7 is a deubiquitinating enzyme, and its deubiquitinating activity is usually explored in research to maintain protein stability. However, it has been reported that USP7 can interact with PcG proteins to regulate molecular transcription [ 78 ]. Thus, the regulation of NLGN3 by USP7 may not only indirectly promote NLGN3 transcription by stabilizing KPNB1 expression by deubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, expression of primitive endoderm-associated genes is hindered. Despite these findings, it remains to be established whether these newly identified functions of USP7 play a critical role in the early stages of embryonic development ( Liu et al, 2023 ) and whether USP7 is able to modulate other cellular processes in a non-catalytic manner.…”
Section: Non-catalytic Functions Of Dubs and Ubl Proteasesmentioning
confidence: 99%